Evaluation of a rare known anatomic formation: Parinaud’s canal - Guldane MAGAT; Sultan UZUN (Scientific Reports)
Abstract Parinaud’s canal (PC) is a structure located on the processus frontalis ossis maxilla. During the growth period, the shape of the nasal septum and the presence of nasal septal deviation (NSD) may affect facial morphological parameters. The aim of this study is to investigate the presence of PC and the effect of the NSD on facial morphological parameters. Radiographic images of 200 patients were retrospectively reviewed. On the CBCT images PC, NSD and Palate-Orbita angle were evaluated. The significance level was set at p = 0.05. PC was found to be present at a high rate in the general population and its presence was not significantly different according to the angle of nasal deviation (p > 0.05). The angle of NSD was found to increase statistically when the left PC diameter was 1 mm or less (p < 0.05). The mean Hard Palate - Orbital Angle was 46.66 ± 8.43 degrees in individuals with the right PC while this angle was 36.50 ± 1.65 degrees in those without a canal. his study revealed that PC is common in the general population and has no significant relationship with NSD angle. While a decrease in the diameter of the left Parinaud’s canal is observed as the NSD increases, the Hard Palate - Orbital Angle varies depending on the presence of the right PC. These findings indicate PC may play an important role in nasal and orbital anatomy.